Active and Stable Nickel‐Based Electrocatalysts Based on the ZnO:Ni System for Water Oxidation in Alkaline Media. Issue 4 (11th October 2016) - Pfrommer, Johannes; Azarpira, Anahita; Steigert, Alexander; Olech, Katarzyna; Menezes, Prashanth W.; Duarte, Roberto Félix; Liao, Xiaxia; Wilks, Regan G.; Bär, Marcus; Schedel‐Niedrig, Thomas; Driess, Matthias
Abstract: The synthesis of monodisperse, surfactant‐free, Ni‐substituted ZnO nanocrystallites (ZnO:Ni) by the mild solvolysis of heterobimetallic Ni4− x Zn x O4 cubane‐like precursors ( x =1–3) in benzylamine is reported. Ni4− x Zn x O4 was grafted by electrophoretic deposition onto fluorine‐doped tin oxide glass substrates and used as an active and stable working electrode for water oxidation. Upon the application of a voltage at the electrodes, the ZnO:Ni precatalyst leads to an active composite material that can oxidize water (>15 h) with an increasing catalytic current. In contrast, the performance of homometallic NiO reference materials decreases rapidly over time and is surpassed by the composite from the ZnO:Ni precatalyst in terms of both stability and activity. Extensive characterization of the as‐prepared and activated ZnO:Ni precatalyst by using hard X‐ray photoelectron spectroscopy revealed that the excellent performance of the electrode material is because of the formation of a unique self‐supported turbostratically disordered mixture of γ‐NiOOH/α‐Ni(OH)2 ‐like phases from the rapid dissolution of Zn II in the ZnO:Ni precatalyst into the electrolyte during activation. Abstract : Activation by substitution : A solvolytic route to synthesize a monodisperse Ni‐substituted ZnO (ZnO:Ni) nanocrystalline precatalyst is realized from heterobimetallic cubane‐like precursors that subsequently exhibits superior catalytic activity and prolonged stability for the electrochemical water oxidation in alkaline media.